Analisis Kinerja Pegawai Sebelum Dan Sesudah Penerapan Kebijakan Penilaian Prestasi Kerja Berbasis SKP (Sasaran Kerja Pegawai) - Tajeri, Tajeri (Sekolah Tinggi Ilmu Ekonomi Muara Teweh, 2020)
This study aims to determine the performance of employees before implementing the SKP-based work performance appraisal policy (Employee Work Target) at the Muara Teweh City Regional Secretariat, how is the employee performance after implementing the SKP-based work performance appraisal policy (Employee Work Target) at the Regional Secretariat of Muara Teweh City is there a difference in the performance of the PNS of the Regional Secretariat of the City of Muara Teweh before and after the policy of implementing the SKP-based PNS work performance assessment. This research method using this research is descriptive quantitative research, data obtained from a sample of the study population were analyzed according to statistical methods. The results of data collection are obtained. Given the reference value sig (2-tailed) in the above table display, the t value is 11.375 with sig 0.000 because sig <0.005, it can be concluded that H0 is rejected, meaning that the average respondent's answer before and after SKP is not the same (different), while H1 was accepted because the results of respondents' answers before and after the SKP were not the same. The research results concluded. There are differences in employee performance before and after the implementation of the SKP-based employee performance appraisal policy at the Regional Secretariat of Muara Teweh City.